Disorders of Motor-evacuation Function of the Colon in Children - G.B. Bodnar (Zaslavsky O.Yu., 2012)
The article presents the results of clinical examination of children with chronic constipations on a background of colonic abnormalities. There were marked out groups with the pathogenic types of colostasis: сologenic, proctogenic, сoloproctogenic (mixed). The article explains the importance of the full examination of children with chronic constipation.